Efficiency as an Intervening Factor in the Relationship between Credit Risk and Liquidity on Profitability - Selah Azizah; Emmanuel Kristijadi (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
This study aims to analyze the effect of credit risk and liquidity risk on profitability, with efficiency as an intervening variable. This study uses descriptive analysis methods, multiple linear regression analysis, path analysis, and the Sobel test. The population used is BUSN Foreign Exchange and the sample used in this study is all BUSN Foreign Exchange for the 2019-2023 period. The analysis results show that NPL has a significant negative effect on Efficiency. ALR has a positive but insignificant effect on Efficiency. NPL has a significant negative effect on ROA. ALR has a positive but insignificant effect on ROA. Efficiency has a significant positive effect on ROA. NPL has a significant effect on ROA, with Efficiency as an intervening variable. ALR has a significant effect on ROA, and ALR has a significant effect on ROA, with Efficiency as an intervening variable. This study emphasizes the need for banks to strengthen their credit risk management systems while simultaneously improving cost efficiency through digitalization, controlling overhead costs, and improving human resource productivity. Keywords: Credit Risk; Liquidity Risk; Profitability; Efficiency; Bank